Development of Class IIa Bacteriocins as Therapeutic Agents - Christopher T. Lohans; John C. Vederas (International Journal of Microbiology)
Class IIa bacteriocins have been primarily explored as natural food preservatives, but there is much interest in exploring the application of these peptides as therapeutic antimicrobial agents. Bacteriocins of this class possess antimicrobial activity against several important human pathogens. Therefore, the therapeutic development of these bacteriocins will be reviewed. Biological and chemical modifications to both stabilize and increase the potency of bacteriocins are discussed, as well as the optimization of their production and purification. The suitability of bacteriocins as pharmaceuticals is explored through determinations of cytotoxicity, effects on the natural microbiota, and in vivo efficacy in mouse models. Recent results suggest that class IIa bacteriocins show promise as a class of therapeutic agents.